Autonomic and cardiac evaluation upon sub-therapeutic doxorubicin administration. (14th October 2021) - Amaro-Leal, Â; Machado, F; Afonso, A I; Rocha, I; Geraldes, V
Abstract:  : Doxorubicin (DOX) is a chemotherapeutic agent that improves the survival and quality of life of patients with solid tumours. However, these improvements are counterbalanced by various dose-dependent side effects including cardiac dysfunction, which may occur in a subset of patients leading to treatment discontinuation. In addition, despite overall insufficiently studied, available data clearly show that women are more susceptible to drugs toxicity due to sex differences in drug metabolism or sensitivity. Regarding doxorubicin, apart its acute toxicity, women are also more vulnerable to late cardiotoxicity. Currently, there are no robust clinical imaging techniques or biomarkers available to detect DOX-cardiotoxicity before functional decline and, despite treatment personalization, subclinical signs of toxicity are not yet well identified. Thus, in the present work, we sought to characterize the toxic effects of a sub-therapeutic dose of doxorubicin upon cardiovascular and autonomic function. For that, adult healthy female wistar rats (n=14), aged >3 months, were intraperitoneally treated with doxorubicin (2 mg/kg) at weekly intervals for up to 4 weeks. A control (Ctrl, n=7) group received saline solution 0, 9% NaCl as a vehicle. Rats underwent an echocardiographic evaluation at 4 weeks. Blood pressure, heart rate and respiratory frequency were assessed in an acute experiment. Cardiovascular variability studies in the time-frequency domain (LF, HF and LF/HF calculation) and cardiorespiratory reflexes assessment were performed. T-Student test for paired observations was applied (level significance p<0.05) DOX-treated animals showed a severe bradypnea and hypotension, significant decrease in ejection fraction and fractional shortening, sympatho-inhibition and reduced baroreceptor reflex gain and chemoreflex sensitivity. Our functional results might be due to cellular respiratory dysfunction and vascular adaptations induced by doxorubicin via TNF alpha actions at central nervous system (CNS) and peripheral level. In fact, peripheral TNF alpha release elicits NO production, which through vasodilation will induce hypotension and baroreceptor reflex adjustments. Reinforcing these actions, and despite doxorubicin low ability to pass BBB, TNF alpha acting at CNS induces neuronal apoptosis and impairment of mitochondrial function which might also contribute to affect autonomic and respiratory function, expressed by a decreased chemoreflex sensitivity and sympathetic tone. In conclusion, sub-therapeutic doses of doxorubicin are able to produce per se the impairment of autonomic and cardiac functions. Thus, a tight monitoring of these functions in patients treated with therapeutic doses of doxorubicin is highly recommended. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fundação para a Ciência e a Tecnologia